AB0115 Scleroderma-like changes in a diabetic patient: a clinical case. (1st June 2001) - Cruz, M; de Matos, A Alves; Branco, JC
Abstract : Background: Diabetes mellitus is a metabolic systemic disease that can be associated, particularly when glucose metabolism control is poor, with skin changes and sometimes finger contractures of the hands that clinically resemble scleroderma. Distinction between the two different conditions is important, because they have distinct therapeutic approach and prognostic. A 55 year-old white woman came to our Unit because of skin changes and articular contractures. She had diabetes mellitus since a gestation eleven years ago and was being followed in the Endocrinology department for this reason. Her disease had been resistant to antidiabetic oral treatment and was complicated with a severe polyneuropathy in glove and stoking pattern. Control of glucose metabolism was poor and she was being teached to start insulin therapy. She had been also diagnosticated of an autoimmune tiroiditis and recent arterial hypertension. We observed a thin woman wiyh yight shiny skin over her fingers and unreduceable contractures of some of them in both hands. The skin of her distal legs was billaterally swelled and sclerotic too. She refered a Raynaud fenomenon, which we weren´t able to provoque with cold water. There were no other musculoskeletal findings or symptoms suggesting CREST or systemic disease beyond diabetes. Her ANA and anti-DNA were negative, as was anticentrome antibody and Scl70. The hand x-rays showed neither calcifications nor erosions. A capilaroscopy was performed, showing some megacapilaries and structural disorganisation. No avascular areas were found. We concluded, in face of the analytic results, that this was a scleroderma-like manifestation of diabetic cheiroarthropathy and not systemic or limited scleroderma. The changes seen in the capilaroscopy could be due to the cheiroarthropathy itself. Objectives: Methods: Results: Conclusion: